2016
DOI: 10.2147/nss.s71970
|View full text |Cite|
|
Sign up to set email alerts
|

Unihemispheric sleep and asymmetrical sleep: behavioral, neurophysiological, and functional perspectives

Abstract: Sleep is a behavior characterized by a typical body posture, both eyes’ closure, raised sensory threshold, distinctive electrographic signs, and a marked decrease of motor activity. In addition, sleep is a periodically necessary behavior and therefore, in the majority of animals, it involves the whole brain and body. However, certain marine mammals and species of birds show a different sleep behavior, in which one cerebral hemisphere sleeps while the other is awake. In dolphins, eared seals, and manatees, unih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 121 publications
1
34
0
Order By: Relevance
“…However, since the cortical distribution of slow-wave origins was not systematically and significantly affected by the resection of the CC, the observed asymmetry could be entirely explained by the reduced cross-hemispheric slow-wave propagation. This observation is in line with previous evidence suggesting that the lack or resection of inter-hemispheric connections is not sufficient for the manifestation of unihemispheric sleep ( Berlucchi, 1966 ; Montplaisir et al, 1990 ; Nielsen et al, 1993 ), as naturally seen in some animal species, such as birds and cetaceans ( Rattenborg et al, 2000 ; Mascetti, 2016 ). On the other hand, the absence (as in birds) or small size (as in cetaceans; Tarpley and Ridgway, 1994 ) of the CC may prevent the cross-hemispheric spreading of sleep slow waves, and thus represent one fundamental prerequisite for unihemispheric sleep.…”
Section: Discussionsupporting
confidence: 92%
“…However, since the cortical distribution of slow-wave origins was not systematically and significantly affected by the resection of the CC, the observed asymmetry could be entirely explained by the reduced cross-hemispheric slow-wave propagation. This observation is in line with previous evidence suggesting that the lack or resection of inter-hemispheric connections is not sufficient for the manifestation of unihemispheric sleep ( Berlucchi, 1966 ; Montplaisir et al, 1990 ; Nielsen et al, 1993 ), as naturally seen in some animal species, such as birds and cetaceans ( Rattenborg et al, 2000 ; Mascetti, 2016 ). On the other hand, the absence (as in birds) or small size (as in cetaceans; Tarpley and Ridgway, 1994 ) of the CC may prevent the cross-hemispheric spreading of sleep slow waves, and thus represent one fundamental prerequisite for unihemispheric sleep.…”
Section: Discussionsupporting
confidence: 92%
“…Similar unihemispheric sleep patterns have been observed in several species of whales, manatees, some seals as well as several birds [6,7]. Although unihemispheric sleep does not occur in humans, a recent study has shown that during the first night in a laboratory environment, the left hemisphere displays less SWA and is more reactive to external stimuli compared to the right hemisphere, potentially acting as a ‘night watch’ to monitor unfamiliar surroundings [8 • ].…”
Section: Local Aspects Of Sleepmentioning
confidence: 61%
“…Such regional aspects of sleep activity had already been observed in certain animal species (e.g. dolphins who can enter unihemispheric sleep, sleeping in one brain hemisphere at a time) (Mascetti, Gian Gastone, 2016;Rattenborg et al, 2019) and in sleep pathologies (Castelnovo et al, 2016;Dodet et al, 2015;Riedner et al, 2016;Terzaghi et al, 2009). However, in the past few years, local sleep involving changes in sleep depth within NREM sleep has been robustly observed in individuals without sleep disorders (Huber et al, 2004;Nir et al, 2011).…”
Section: Introductionmentioning
confidence: 80%